Analisis Aspek Hukum UU Nomor 17 Tahun 2023 dalam Upaya Penurunan Angka Kematian Ibu Dan Bayi di Indonesia: Tinjauan Litelatur - Auliya, Viona Shafa; Saragih, Yaamirah Mandasari; Pardosi, Manahap Cerarius Fransiskus; Sinaga, Toga Adi Putra; Pasaribu, Alza Hamonangan (Hukum dan Dinamika Masyarakat, 2025)
The 2030 Agenda for Sustainable Development agreed upon at the UN General Assembly emphasizes the importance of the Sustainable Development Goals (SDGs) as a global framework for sustainable development. In Indonesia, maternal and child health is a key focus, particularly in SDGs 4 and 5, which aim to reduce child mortality and improve maternal health. The high maternal and infant mortality rates in Indonesia, as indicated by the Maternal Mortality Rate (MMR), highlight the low level of public health. The causes of maternal mortality in Indonesia include hemorrhage, infection, and hypertension, which significantly contribute to health issues. The implementation of Law No. 17 of 2023 focuses on improving postpartum and reproductive health services to reduce maternal and infant mortality rates. This article discusses the importance of improving postpartum health services for mothers as a strategic step toward achieving better health outcomes in Indonesia.The 2030 Agenda for Sustainable Development agreed upon at the UN General Assembly emphasizes the importance of the Sustainable Development Goals (SDGs) as a global framework for sustainable development. In Indonesia, maternal and child health is a key focus, particularly in SDGs 4 and 5, which aim to reduce child mortality and improve maternal health. The high maternal and infant mortality rates in Indonesia, as indicated by the Maternal Mortality Rate (MMR), highlight the low level of public health. The causes of maternal mortality in Indonesia include hemorrhage, infection, and hypertension, which significantly contribute to health issues. The implementation of Law No. 17 of 2023 focuses on improving postpartum and reproductive health services to reduce maternal and infant mortality rates. This article discusses the importance of improving postpartum health services for mothers as a strategic step toward achieving better health outcomes in Indonesia.